Transabdominal 2-Dimensional Shear-Wave Elastography for Diagnostic Differentiation Between Adenomyosis Leiomyoma and Normal Myometrium - Kaya Narcicegi, Veziha; Aslan, Melike; Artas, Hakan; Eryesil, Hasan; Yavuzkir, Seyda; Yurt, Nurdan; Ozercan, Ibrahim Hanifi (Sage Publications Inc, 2023)
Objective: Shear-wave elastography (SWE) can be used to obtain quantitative information about tissue stiffness. This study compared SWE measurements of patients with adenomyosis, leiomyoma, and normal myometrium.Materials and Methods: This study included 56 women who were scheduled to undergo hysterectomy. Measurements of the uterine myometrium and leiomyomas, if any, of the patients were preoperatively collected through SWE. A total of 69 SWE measurements were included.Postoperatively, the patients were categorized according to the results of histopathologic examinations: group 1 included patients with normal myometrium; group 2 included those with adenomyosis; and group 3 included those with leiomyomas. The Emean values of the kPa obtained from the SWE measurements were compared with the histopathologic results.Results: The SWE measurements of groups 2 and 3 were significantly higher than those of group 1. There were no significant differences between groups 2 and 3 in mean SWE measurements. The success rate of SWE in differentiating normal myometrium and adenomyosis was 92%, with a sensitivity of 93.1% and a specificity of 82.1%.Conclusion: This study revealed that using ultrasound elastography to diagnose adenomyosis is successful in distinguishing that condition from normal myometrium, but SWE is not useful for distinguishing adenomyosis leiomyoma. (J GYNECOL SURG 20XX:000)
Keywords: adenomyosis; leiomyoma; shear-wave elastography; normal myometrium